Different aspects of a living heritage: spice bazaar in Istanbul - Durhan, S.; Ozguven, Y. (GREEN LINES INST SUSTAINABLE DEVELOPMENT, 2010)
Spice Bazaar dated to 17th century, has been constructed as arasta of Yeni Cami Mosque complex in Historical Peninsula, Istanbul. The bazaar has a significant role in urban history by architectural, environmental, social, cultural and economical aspects. It has always served to the city as a spice market by sustaining original function for 400 years. Nevertheless, today the bazaar building is threatened by new additions closing the main facade and unhealthiness. It is impossible to deny the role of the bazaar in the urban sustainable development as a living heritage. By considering the fact that having a role on social life as urban heritage not only as touristic heritage, only if, it would have better conditions on the purpose of use by keeping original structure as a spice bazaar and if the environmental life qualities increased, it could have a possibility for contributing to urban development.
Keywords: Cultural Studies; Business & Economics; Environmental Sciences & Ecology; Public Administration